Did Universal Access to ARVT in Mexico Impact Suboptimal Antiretroviral Prescriptions?. (11th December 2013) - Caro-Vega, Yanink; Volkow, Patricia; Sierra-Madero, Juan; Colchero, M. Arantxa; Crabtree-Ramírez, Brenda; Bautista-Arredondo, Sergio
Abstract : Background . Universal access to antiretroviral therapy (ARVT) started in Mexico in 2001; no evaluation of the features of ARVT prescriptions over time has been conducted. The aim of the study is to document trends in the quality of ARVT-prescription before and after universal access. Methods . We describe ARVT prescriptions before and after 2001 in three health facilities from the following subsystems: the Mexican Social Security (IMSS), the Ministry of Health (SSA), and National Institutes of Health (INS). Combinations of drugs and reasons for change were classified according to current Mexican guidelines and state-of-the-art therapy. Comparisons were made using χ 2 tests. Results . Before 2001, 29% of patients starting ARVT received HAART; after 2001 it increased to 90%. The proportion of adequate prescriptions decreased within the two periods of study in all facilities (P value < 0.01). The INS and SSA were more likely to be prescribed adequately (P value < 0.01) compared to IMSS. The distribution of reasons for change was not significantly different during this time for all facilities (P value > 0.05). Conclusions . Universal ARVT access in Mexico was associated with changes in ARVT-prescription patterns over time. Health providers' performance improved, but not homogeneously. Training of personnel and guidelines updating is essential to improve prescription.